Angular coefficients of Z bosons produced in pp collisions at root S=8 TeV and decaying to mu(+)mu(-) as a function of transverse momentum and rapidity - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; Hartl, C.; Hoermann, N.; et al. (Elsevier B.V., 2015)
Measurements of the five most significant angular coefficients, A(0) through A(4), for Z bosons produced in pp collisions at root S = 8 TeV and decaying to mu(+)mu(-) are presented as a function of the transverse momentum and rapidity of the Z boson. The integrated luminosity of the dataset collected with the CMS detector at the LHC corresponds to 19.7 fb(-1). These measurements provide comprehensive information about the Z boson production mechanisms, and are compared to the QCD predictions at leading order, next-to-leading order, and next-to-next-to-leading order in perturbation theory. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.
Keywords: CMS; Physics; Z boson production